2012
DOI: 10.1007/s11096-012-9620-8
|View full text |Cite
|
Sign up to set email alerts
|

Errors in fluid therapy in medical wards

Abstract: Our result showed that intravenous fluid therapy errors occurred commonly in the hospitalized patients especially in the medical wards. Improvement in knowledge and attention of health-care workers about these errors are essential for preventing of medication errors in aspect of fluid therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 21 publications
1
19
0
1
Order By: Relevance
“…Of the 15 studies on administration error, only 2 (13.33%) provided specific definitions for administration errors [20,32]. Three studies out of 6 (50%) on prescribing error used specific definitions [16,20,22]. Definitions for transcribing error were provided in two out of 3 studies (66.7%) [25,32].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 15 studies on administration error, only 2 (13.33%) provided specific definitions for administration errors [20,32]. Three studies out of 6 (50%) on prescribing error used specific definitions [16,20,22]. Definitions for transcribing error were provided in two out of 3 studies (66.7%) [25,32].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported findings on severity of MEs [16,22,32]. For categorizing MEs and determining the severity of them, 2 studies used National Coordinating Council for Medication Error Reporting and Prevention (NCC MERP) Index [16,32]; the other one used definitions and leveling provided by Hartwig, Denger, and Schneider [22].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Inappropriate intravenous fluid management is common and known to contribute to a significant proportion of iatrogenic morbidities and mortalities. 1,3,4,6,9 This is especially important in patients with reduced physiological reserves, including elderly patients and those with cardiac or renal failure. 6,1012 Despite the clear importance of appropriate intravenous fluid prescription, such practice is often left to be undertaken by the most junior doctors in the hospitals, such as the FY1s in the UK.…”
Section: Discussionmentioning
confidence: 99%